Survival after cardiac resynchronization therapy: results from 50 084 implantations. Issue 5 (27th December 2018) - Leyva, Francisco; Zegard, Abbasin; Okafor, Osita; de Bono, Joseph; McNulty, David; Ahmed, Asif; Marshall, Howard; Ray, Daniel; Qiu, Tian
Abstract: Aims: Randomized controlled trials have shown that cardiac resynchronization therapy (CRT) prolongs survival in patients with heart failure. No studies have explored survival after CRT in relation to individuals in the general population (relative survival, RS). We sought to determine observed and RS after CRT in a nationwide cohort undergoing CRT. Methods and results: A national administrative database was used to quantify observed mortality for patients undergoing CRT. Relative survival (RS) was quantified using life tables. In 50 084 patients [age 72.1 ± 11.6 years (mean ± standard deviation)] undergoing CRT with (CRT-D) ( n = 25 273) or without (CRT-P) defibrillation ( n = 24 811) over 8.8 years (median follow-up 2.7 years, interquartile range 1.3–4.8), expected survival decreased with age. Device type, male sex, ischaemic heart disease, diabetes, and chronic kidney disease predicted excess mortality. In multivariate analyses, excess mortality (analogue of RS) was lower after CRT-D than after CRT-P in all patients [adjusted hazard ratio (aHR) 0.80, 95% confidence interval (CI) 0.76–0.84] as well as in subgroups with (aHR 0.79, 95% CI 0.74–0.84) or without (aHR 0.82, 95% CI 0.74–0.91) ischaemic heart disease. A Charlson Comorbidity Index (CCI) ≥3 portended a higher excess mortality (aHR 3.04, 95% CI 2.76–3.34). Relative survival was higher in 2015–2017 than in 2009–2011 (aHR 0.64, 95% CI 0.59–0.69). Conclusion: Reference RS data after CRT is presented. Sex, ischaemic heart disease, diabetes, chronic kidney disease, and CCI were major determinants of RS after CRT. CRT-D was associated with a higher RS than CRT-P in patients with or without ischaemic heart disease. Relative survival after CRT improved from 2009 to 2017.